#TITLE_ALTERNATIVE# - RAMADHAN PRIBADI (NIM : 10213101), NAUFAL
Plasmonic material is an alternative constituent material for optoelectronic devices, which utilizes physics phenomena of surface plasmon as working principle. Some examples of the plasmonic material application such as biosensor, solar cell, photodetector, and etc. In this research, we have investigated plasmonic state of Cu thin films on plasmon energy and dielectric constant changed with varying thickness of thin films and treating hydrogen plasma annealing. Cu thin films were deposited on SiO2 substrate using thermal evaporation method on three samples with different thickness, obtained rough topography and metal islands-like on sample surface, and after treated by hydrogen plasma annealing, surface has smoothened and metal islands has removed. Sample was characterized using spectroscopic ellipsometry in the energy ranges 0.6 Ã‚Â– 6.5 eV, and measurement results are extracted by optical model fitting of measurement results using CompleteEASE software into dielectric constant and energy loss function values. Energy loss function shows Cu thin films surface plasmon energy value. Cu thin films surface plasmon energy is shifted to lower energy (redshift) due to higher thickness. Effect of hydrogen plasma annealing on Cu thin films removed localized surface plasmon which arise after deposition using thermal evaporation method, and surface plasmon energy is shifted to the higher energy (blueshift).